2008
DOI: 10.1161/circresaha.107.169755
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ /Calmodulin-Dependent Protein Kinase IIδ and Protein Kinase D Overexpression Reinforce the Histone Deacetylase 5 Redistribution in Heart Failure

Abstract: Abstract-Cardiac hypertrophy and heart failure (HF) are associated with reactivation of fetal cardiac genes, and class II histone deacetylases (HDACs) (eg, HDAC5) have been strongly implicated in this process. We have shown previously that inositol trisphosphate, Ca 2ϩ /calmodulin-dependent protein kinase II (CaMKII), and protein kinase (PK)D are involved in HDAC5 phosphorylation and nuclear export in normal adult ventricular myocytes and also that CaMKII␦ and inositol trisphosphate receptors are upregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 42 publications
7
102
2
1
Order By: Relevance
“…CaMKII δ isoforms couple to ERK1/2 signaling [1,47], and the δ 2 isoform was shown to specifically regulate VSMC migration [105,108]. Upregulation of CaMKII δ isoforms was shown to occur in models of cardiac hypertrophy and heart failure [23,166], as well as in regenerating skeletal muscle after injury [2].…”
Section: Decrease Of Camkiiγ and Increase Of Camk Iiδmentioning
confidence: 99%
“…CaMKII δ isoforms couple to ERK1/2 signaling [1,47], and the δ 2 isoform was shown to specifically regulate VSMC migration [105,108]. Upregulation of CaMKII δ isoforms was shown to occur in models of cardiac hypertrophy and heart failure [23,166], as well as in regenerating skeletal muscle after injury [2].…”
Section: Decrease Of Camkiiγ and Increase Of Camk Iiδmentioning
confidence: 99%
“…In the heart, PKD1 has been best characterized for its role in regulating myocardial contraction, cardiac hypertrophy and remodeling (27,28). PKD1 is a typical HDAC5 kinase and thus more relevant to HDAC5-MEF2 hypertrophic signaling (19,29). Mice with PKD1 ablation show substantial resistance to cardiac hypertrophy (30).…”
Section: Pathological Cardiac Hypertrophy (Pch)mentioning
confidence: 99%
“…Indeed, it has been demonstrated that the release of perinuclear IP 3 -sensitive Ca 2+ stores promotes a CaMKII-dependent phosphorylation of histone deacetylase 5 (HDAC5) thereby causing it to be exported out of the nucleus [140]. Thus, perinuclear IP 3 -evoked Ca 2+ signals can derepress the expression of genes that underlie hypertrophic growth, such as those under the control of MEF2c [149]. It is well known that stimulation of myocytes with hormones that activate IP 3 production, e.g.…”
Section: Ip 3 Signaling In Ventricular Myocytesmentioning
confidence: 99%